2022
DOI: 10.17309/tmfv.2022.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Development Self-Assessment Indicators on Value Orientation Structure Formation in Senior School Age Students

Abstract: Background. Physical education as a subject in general secondary education institutions aims not only to solve health and educational problems but also to form a value attitude to health, healthy lifestyle, fostering the interest in and the need for physical activity. Research purpose. The study aims to investigate the relationship between senior school age students’ value orientations and physical development self-assessment indicators to determine incentives to increase motivation for self-improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…For an adolescent who is in the phase of psychological and social development, the figure and character of the idol will color the shaping of his attitudes and values, including the shaping of sportsmanship. This is because various aspects of value orientation formation have relevance to activities in physical culture and sports (Bakiko et al, 2022). A positive value orientation will at least prevent someone from cheating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For an adolescent who is in the phase of psychological and social development, the figure and character of the idol will color the shaping of his attitudes and values, including the shaping of sportsmanship. This is because various aspects of value orientation formation have relevance to activities in physical culture and sports (Bakiko et al, 2022). A positive value orientation will at least prevent someone from cheating.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the use of information through digital media, there is a health study that states that various results from searching for information on the Internet are most strongly predicted by gender (Rice, 2006). Another study found that boys and girls showed differences in indicators of selfesteem, physical development, and priority in the choice of value orientation (Bakiko et al, 2022). So for future research, we recommend it to test the exposure of athletic performance information on the formation of adolescent attitudes in several categories, for example, based on gender.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms the importance of family in the formation of a healthy lifestyle, communication skills, social integration, and the formation of such positive psychological aspects as self-esteem and moral values. Internal and external factors influence the organization and content of family leisure (Bakiko et al, 2022). We have updated the information on factors of external influence, that is the dependence of family leisure time on the workload and professional activity of parents, previous physical activity experience, family type (in accordance with the period of being officially married), an unformed culture of family leisure, lifestyle, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The entertainment industry has become one of the most important areas of society's everyday life. A significant number of scientists have devoted their research to the issue of the development of the entertainment and recreation industry using the means of health-improving and recreational physical activity (HRPA) (Bakiko et al, 2022;Grygus, 2017;Krutsevich et al, 2019). The results of modern scientific research demonstrate numerous advantages of using active leisure for the integral development of the emotional, cognitive, physical, and social abilities of young people (Freire, 2018;Rodríguez, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Дослідження динаміки формування та засвоєння цінностей, проведене науковцями [14], показало, що у дітей до 10 років цінності співпадають із цінностями батьків, а вже у віці 11-14 років збіг цінностей, які декларуються батьками та підлітками, значно зменшується. Науковцями наголошується, що врахування ціннісних орієнтирів є важливим при залученні школярів до регулярних занять фізичними вправами, підвищенні рівня їх рухової активності [4,13]. Формування ціннісних орієнтацій було предметом дослідження науковців, якими зверталася увага на їхні відмінності залежно від віку, статі, гендерних особливостей [4,10,12,15].…”
Section: Introductionunclassified